Pre-season dietary intake of professional soccer players. Issue 4 (December 2017) - Raizel, Raquel; da Mata Godois, Allan; Coqueiro, Audrey Yule; Voltarelli, Fabrício Azevedo; Fett, Carlos Alexandre; Tirapegui, Julio; de Paula Ravagnani, Fabricio Cesar; de Faria Coelho-Ravagnani, Christianne
Background: Despite the well-documented importance of nutrition in optimizing performance and health, the dietary intake of soccer players has attracted little attention. Aim: We aimed to assess the pre-season dietary intake of professional soccer players and its adequacy in macro and micronutrients. Methods: The pre-season dietary intake of 19 male athletes was assessed using a semi-structured 3-day food record. To determine dietary adequacy and excess, energy and macronutrient intake were compared with the Brazilian dietary reference values for athletes, and micronutrients were compared with the Estimated Average Requirement – EAR (minimum recommendation) and Tolerable Upper Intake Level – UL (maximum recommendation). Results: Mean daily energy intake (40.74±12.81 kcal/kg) was adequate. However, there was a low carbohydrate intake (5.44±1.86 g/kg/day) and a high amount of protein and fat (1.91±0.75 and 1.27±0.50 g/kg/day, respectively). Sodium intake (3141.77±939.76 mg/day) was higher than UL (2300 mg/day), while the majority of players showed daily intake of vitamin A (74%), vitamin D (100%), folate (58%), calcium and magnesium (68%) below the EAR (625, 10 and 320 µg/day, 800 and 330 mg/day, respectively). Conclusion: The dietary intake of professional soccer players was adequate in energy, but inadequate in macro and micronutrients, which suggests the need to improve nutritional practices to sustain the physical demands of soccer during pre-season.